Distribusi spasial komunitas makrozoobentos di Sungai Cilalawi Kabupaten Purwakarta, Jawa Barat - Hana Septiani Suminar; Zahidah Zahidah; Herman Hamdani; Asep Sahidin (Depik, 2020)
Reservoir inlet. The Cilalawi River receives pollutant from households, as well as agriculture around the river. Utilization of the river as a waste disposal site is the impact of community activities on the environment that causes changes in environmental factors that will adversely affect the life of aquatic organisms. This research aims to map the spatial distribution of macrozoobenthos community along the Cilalawi River. This research was conducted from March-May 2019. The research method used a survey method by taking water and macrozoobenthos samples along the Cilalawi River. Data collection techniques using purposive sampling by setting 4 stations and four times sampling every two weeks. Based on the observation location, composition at station 1 consisted of 3 classes and 12 species of macrozoobenthos. The composition at station 2 consists of 3 classes and 10 species. Composition at station 3 consists of 3 classes and 16 species and composition at station 4 consists of 2 classes and 7 species. The difference in species deficit value at each station is different, this is influenced by physical and chemical parameters according to conditions around the aquatic environment. The index of diversity in the Cilalawi River ranges from 1,59 2,94 and the Uniformity Index of the Cilalawi River ranges from 0,2 to 0,9. The distribution pattern of makrozoobentos in the waters of the Cilalawi River based on the Morisita Index is uniform and grouped at station 1 to station 4Keywords:Distribution,Makrozoobenthos,Cilalawi River,Jatiluhur,PollutantABSTRAKSungai Cilalawi merupakan salah satu anak Sungai Citarum yang menjadi inlet Waduk Jatiluhur. Sungai Cilalawi menerima buangan limbah yang berasal dari rumah tangga, serta pertanian yang berada di sekitar aliran sungai. Pemanfaatan Sungai untuk pembuangan limbah merupakan dampak dari aktivitas masyarakat terhadap lingkungan yang menyebabkan perubahan faktor lingkungan yang akan berakibat buruk bagi kehidupan organisme air. Riset ini bertujuan untuk memetakan distribusi spasial makrozoobentos di sepanjang aliran Sungai Cilalawi. Riset ini dilakukan dari bulan Maret Mei 2019. Metode riset menggunakan metode survey yaitu dengan cara melakukan pengambilan sampel air dan sampel makrozoobentos di sepanjang Sungai Cilalawi. Teknik pengambilan data menggunakan purposive sampling dengan menetapkan 4 stasiun dan empat kali pengambilan sampling setiap dua minggu sekali. Berdasarkan lokasi pengamatan secara komposisi di stasiun 1 terdiri dari 3 kelas dan 12 spesies makrozoobentos. Komposisi di stasiun 2 terdiri dari 3 kelas dan 10 spesies. Komposisi di stasiun 3 terdiri dari 4 kelas dan 16 spesies dan komposisi di stasiun 4 terdiri dari 2 kelas dan 7 spesies. Perbedaan nilai spesies defisit pada masing masing stasiun berbeda, hal ini dipengaruhi oleh parameter fisik dan kimiawi sesuai kondisi di sekitar lingkungan perairan tersebut. Indeks keanekaragaman di Sungai Cilalawi berkisar 1,59 2,94 dan Indeks Keseragaman berkisar 0,2 0,9. Pola distribusi makrozoobentos di perairan Sungai Cilalawi berdasarkan Indeks Morisita adalah seragam dan berkelompok di stasiun 1 hingga stasiun 4.Kata kunci:Distribusi, Makrozoobentos, Sungai Cilalawi, Jatiluhur, Bahan Pencemar